Dari Akses ke Aksi: Mendorong Kontribusi Psikologi Indonesia Melalui APA PsycTests® - Siaputra, Ide Bagus; Abraham, Juneman (Faculty of Psychology, Universitas Surabaya, 2025)
The renewed memorandum of understanding (MoU) between Himpunan Psikologi Indonesia (HIMPSI; Indonesian Psychological Association) and the American Psychological Association (APA), originally signed in 2020 and updated in 2025, marks a significant opportunity for Indonesian psychology to expand its contribution on the global stage. This editorial highlights the underrepresentation of Indonesian-language psychological assessments in the APA PsycTests® database and identifies structural barriers, such as the absence of a standardized national documentation system. By showcasing the vast potential of locally developed and adapted psychological tools, this article proposes concrete strategies to foster active participation from Indonesia and other underrepresented communities in developing evidence-based and contextually relevant psychological science. Proposed strategies include empowering individual researchers to submit locally developed or adapted instruments, encouraging institutions and journals to adopt systematic documentation and reporting standards, and establishing a national task force led by professional associations and consortia to coordinate the registration and certification of psychological tests for inclusion in APA PsycTests®. This editorial serves as an open invitation to join a global dialogue in which psychological science is enriched by diverse voices, cultural contexts, and lived experiences from across the world.